PROBLEMS IN USING INNOVATIVE EDUCATIONAL TECHNOLOGIES IN TEACHING THE SCIENCE OF MOLECULAR GENETICS - Daminov M. A. (Web of Journals Publishing, 2024)
This article analyzes the problems of applying innovative educational technologies to the science of molecular genetics and provides information on ways to solve them.
Keywords: problem-based learning technologies, creative technologies, didactic games, technology (technical map).